Recent advances in the anti-tumor activities of saponins through cholesterol regulation - Jiang, Min; Hong, Chao; Zou, Wenkui; Ye, Zheng; Lu, Lu; Liu, Yun; Zhang, Tong; Ding, Yue (Frontiers in Pharmacology, 2025)
Abnormal cholesterol metabolism has become a popular therapeutic target in cancer therapy. In recent years there has been a surge in interest in the anti-tumor activities of saponins, particularly their ability to disrupt cholesterol homeostasis in tumor cells. Cholesterol regulation by saponins is a complex process that involves multiple mechanisms. However, there are now a notable dearth of comprehensive reviews addressing their anti-tumor effects through cholesterol modulation. This review will explore the intricate mechanisms by which saponins regulate cholesterol, including modulation of synthesis, metabolism, and uptake, as well as complex formation with cholesterol. It will also outline how saponins exert their anti-cancer activities through cholesterol regulation, enhancing cytotoxicity, inhibiting tumor cell metastasis, reversing drug resistance, inducing immunotoxin macromolecule escape, and ferroptosis. This comprehensive analysis offers insights into the potential for the use of saponins anti-tumor therapies and their combinations with other drugs, advancing the understanding of their effects on cancer cells.